Bifunctional circularly-polarized lenses with simultaneous geometrical and propagating phase control metasurfaces. (3rd September 2019) - Li, Haipeng; Wang, GuangMing; Cai, Tong; Liang, JianGang; Hou, Haisheng
Abstract: Achieving different and arbitrary phase distributions for left-handed (LH) and right-handed (RH) circularly polarized (CP) waves, especially in transmission cases, is very important in designing CP lenses. Here, a strategy to control the propagating and geometrical phases simultaneously and independently is proposed by using a four-layered element. The element is a perfect transparent half wavelength plate, which controls the propagating phase by changing the structural size at both orthogonal polarizations and geometrical phase via rotating the structures. To verify the effectiveness of the modulation, we design three linear deflectors by manipulating only propagating phases, only geometrical phases and mix of them to achieve identical, symmetry and asymmetric refractions, respectively. Finally, we simulate and measure lens1 with refractions in different planes and lens2 with pencil-shape and vortex-shape beams. Our findings break the fixed relations of orthogonal CP waves for sole geometrical or propagating metasurface and then offer an effective strategy to achieve arbitrary bifunctional CP devices.